2015
DOI: 10.1007/s10495-015-1151-z
|View full text |Cite
|
Sign up to set email alerts
|

A modified thymosin alpha 1 inhibits the growth of breast cancer both in vitro and in vivo: suppressment of cell proliferation, inducible cell apoptosis and enhancement of targeted anticancer effects

Abstract: Thymosin alpha 1 (Tα1) is commonly used for treating several diseases; however its usage has been limited because of poor penetration of the target tissue, such as tumor cells. In the present study, Tα1-iRGD, a peptide by conjugating Tα1 with the iRGD fragment, was evaluated its performance in MCF-7 and MDA-MB-231 human breast cancer cells. Compared with the wild-type peptide, Tα1-iRGD was more selective in binding tumor cells in the cell attachment assay. Furthermore, the MTT assay confirmed that Tα1-iRGD pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…At the same time, the number of apoptotic cells increased by 22-fold ( Figure 4B). These results are in agreement with the findings of other authors (46,47).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencsupporting
confidence: 94%
See 1 more Smart Citation
“…At the same time, the number of apoptotic cells increased by 22-fold ( Figure 4B). These results are in agreement with the findings of other authors (46,47).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencsupporting
confidence: 94%
“…We then evaluated the effect of chronic treatment with Tα-1 on the proliferation and apoptosis of MCF-7 breast cancer cells. Indeed, various research groups reported that long-term treatment (72 hours) with Tα-1 (in the 150-500 μM concentration range) decreases the proliferation rate of MCF-7 and causes cell apoptosis (46,47). Therefore, we plated MCF-7 at low density on 96-well plates suitable for confocal high-content imaging and evaluated cell proliferation for 72 hours following treatment with Tα-1 (100 ng/ml) or scrambled peptide (100 ng/ml).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencmentioning
confidence: 99%
“…In contrary to our findings, Guo et al indicated that in breast cancer cells, PTEN mediates Thα1‐induced apoptosis by mitochondrial death cascade and suppression of the PI3K/Akt/mTOR signaling pathway . Furthermore, another research suggested that exposure of MCF‐7 cells to Thα1‐iRGD enhanced the apoptotic cells through upregulation of the expression of Bax and caspase 9, which causes to suppress the growth of cancer cells . Fan et al found that after treatment HL‐60, K562, and K562/ADM with Thα1, the features of apoptosis including nuclei condensation and cell morphology appeared …”
Section: Discussioncontrasting
confidence: 99%
“…Thα1 is known as an effective therapeutic peptide for the treatment of some diseases . The major actions of this peptide are activation of cytokines, chemokines, and possessing antifungal as well as antibacterial effects .…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing a different chemotherapeutic, Zhang et al reported that in an A549 xenograft model of non-small cell lung cancer, co-administration of iRGD along with gemcitabine lead to increased penetrance of drug to the tumor and decreased tumor volume over the treatment period of 30 days (Zhang et al, 2015). Finally, Lao et al reported that a thymosin alpha 1-iRGD conjugated form increased apoptosis of MCF-7 cells and decreased tumor volume over an 11 day treatment period when compared to thymosin alpha 1 alone (Lao et al, 2015). …”
Section: Introductionmentioning
confidence: 99%